The Positive Impact of Religiosity on Mental Health in Final Year Students Fatmawati Sukarno State Islamic University Bengkulu - Yuliana, Yuliana (UIN Fatmawati Sukarno Bengkulu, 2022)
This article aims to explain the relationship between religiosity and mental health in final year students at Fatmawati State Islamic University, Sukarno, Bengkulu. The subjects of this study were 102 students at the State Islamic University of Fatmawati Sukarno Bengkulu. Sampling by distributing questionnaires. The results showed that R was 0.459 > 0.05 . This means that the hypothesis is accepted, there is a positive relationship between religiosity and mental health, with an influence value of 0.220 (22%). This means that 22% of religiosity affects a person's mental health and 78% can be influenced by other things, outside of this study.